Hypocortisolemic ASIA: a vaccine- and chronic infection-induced syndrome behind the origin of long COVID and myalgic encephalomyelitis - Ruiz-Pablos, Manuel; Paiva, Bruno; Zabaleta, Aintzane (Frontiers in Immunology, 2024)
Myalgic encephalomyelitis or chronic fatigue syndrome (ME/CFS), long COVID (LC) and post-COVID-19 vaccine syndrome show similarities in their pathophysiology and clinical manifestations. These disorders are related to viral or adjuvant persistence, immunological alterations, autoimmune diseases and hormonal imbalances. A developmental model is postulated that involves the interaction between immune hyperactivation, autoimmune hypophysitis or pituitary hypophysitis, and immune depletion. This process might begin with a deficient CD4 T-cell response to viral infections in genetically predisposed individuals (HLA-DRB1), followed by an uncontrolled immune response with CD8 T-cell hyperactivation and elevated antibody production, some of which may be directed against autoantigens, which can trigger autoimmune hypophysitis or direct damage to the pituitary, resulting in decreased production of pituitary hormones, such as ACTH. As the disease progresses, prolonged exposure to viral antigens can lead to exhaustion of the immune system, exacerbating symptoms and pathology. It is suggested that these disorders could be included in the autoimmune/adjuvant-induced inflammatory syndrome (ASIA) because of their similar clinical manifestations and possible relationship to genetic factors, such as polymorphisms in the HLA-DRB1 gene. In addition, it is proposed that treatment with antivirals, corticosteroids/ginseng, antioxidants, and metabolic precursors could improve symptoms by modulating the immune response, pituitary function, inflammation and oxidative stress. Therefore, the purpose of this review is to suggest a possible autoimmune origin against the adenohypophysis and a possible improvement of symptoms after treatment with corticosteroid replacement therapy.